2012
DOI: 10.1007/s13197-012-0849-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fibers on physico-chemical, sensory and textural properties of Misti Dahi

Abstract: Misti dahi, a popular ethnic delicacy of eastern India analogous to caramel coloured set style sweetened yoghurt, besides several therapeutic virtues, contains high fat and sugar. Alike people elsewhere in the world, people in India too are now becoming health conscious and are aware of the relation between diet and health. Hence, high fat and sugar contents are causes of concern for the successful marketing of misti dahi in India. With a view to enhance the health attributes of misti dahi and improve marketab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
(46 reference statements)
1
30
2
Order By: Relevance
“…Water activity, a physicochemical parameter, is an expression of the amount of water available for biochemical reactions and bacterial growth (Nuzhat et al, ). The increase is water activity may be attributed to the increased expulsion of water (synerisis) from the gel matrix of yogurt due to the presence and interaction of fibers (Raju & Pal, ). The increase in the total bacterial count with the increase in psyllium husk level from T 0 to T 4 may also be due to the prebiotic effect of psyllium husk.…”
Section: Resultsmentioning
confidence: 99%
“…Water activity, a physicochemical parameter, is an expression of the amount of water available for biochemical reactions and bacterial growth (Nuzhat et al, ). The increase is water activity may be attributed to the increased expulsion of water (synerisis) from the gel matrix of yogurt due to the presence and interaction of fibers (Raju & Pal, ). The increase in the total bacterial count with the increase in psyllium husk level from T 0 to T 4 may also be due to the prebiotic effect of psyllium husk.…”
Section: Resultsmentioning
confidence: 99%
“…Perina et al [22] did not find significant differences between the texture of yogurts with passion fruit peel and seeds flour and the control. However, Raju and Pal [21] observed that yogurt fortified with 1.5% of soy fiber or oat fiber present lower scores for texture than the control.…”
Section: Sensory Evaluationmentioning
confidence: 93%
“…To determine syneresis, 100 mL of drinkable yogurt was placed in a graduated cylinder and stored at 5 • C for 28 days. At different times (7,14,21, and 28 days) of storage, the volume of whey was measured. The results were expressed in percentage (%) and were measured as mL of whey per 100 mL initial sample [28].…”
Section: Physicochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This removes any risk of disruption when decanting a sample and allows a more objective measure of semi-solids consistency. However, several authors were used back extrusion test to evaluate the mechanical characterization for many products (i.e., Yoghurt, [10;11;12;13 and 14], Stirred yoghurt; [15;16;17;18;19 and 20], Misti Dahi, [21], Whipped creams; [22], Extruded whey protein concentrate (WPC) and extruded whey protein isolate (WPI); [23], Ricotta cheese; [24] Cottage Cheese; [25], Cooked and canned legumes; [26], Sauces; [27], Custard; [28], Mashed potatoes; [29], Molten chocolate; [30], Food hydrocolloids; [31], Starches such as corn, wheat, and cassava; [32]. …”
Section: Introductionmentioning
confidence: 99%